Integrasi Kompetensi Multikultural dan Keadilan Sosial dalam Layanan Konseling - Hasan Bastomi (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2020)
This study aims to investigate the integration of multikulturalism competence and sosial justice in counseling services. This research belongs to the type of library research, that is, by recording all findings and integrating all findings, both theories or new findings about the integration of the concepts of multikulturalism and sosial justice, analyzing all the findings from various readings and providing critical ideas about the integration of the concepts of multikulturalism and sosial justice in counseling services. The results showed that multikultural counseling is a relationship of counseling on different cultures between counselor and counselee while sosial justice counseling combines cultural responsiveness and understanding the cultural strengths of the client, and focuses on developing strength, empowerment and advocacy. In theoretical and philosophical perspectives that underpin the integration of multikulturalism competencies and sosial justice in counseling services provide a context for developing multikultural competencies and sosial justice counselors. The integration of multikultural concepts and sosial justice recognizes the following as important aspects of counseling practices for counselors and clients, including: (a) understanding the complexity of diversity and multikulturalism in counseling relationships, (b) recognizing the negative effects of sosial oppression on mental health and well-being humans, (c) understand individuals in the context of their sosial environment, and (d) integrate sosial justice assistance into various counseling services (eg, individual, family, sosial, group). So it is necessary to ground the integration of multikultural and sosial justice in counseling services, namely by making academic documents that will apply across populations, services, and client problems.